The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10051037
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease Worsens Short- and Long-Term Outcomes of Systemic Rheumatic Disease Patients Admitted to the ICU: A Multicenter Study

Abstract: Critically ill patients with systemic rheumatic diseases (SRDs) have a fair prognosis, while those with interstitial lung disease (ILD) have a poorer outcome. However, the prognosis of SRD patients with ILD admitted to the intensive care unit (ICU) remains unclear. We conducted a case–control study to investigate the outcomes of critically ill SRD-ILD patients. Consecutive SRD-ILD patients admitted to five ICUs from January 2007 to December 2017 were compared to SRD patients without ILD. Mortality rates were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Rheumatic disease patients are usually considered immunosuppressed due to their underlying, malfunctioning immune system, which sometimes can be further exacerbated by the treatments they receive. A multicenter study in France found that the mortality rate of ILD patients with coexisting systemic rheumatic disease admitted to the intensive care unit was 40% compared to 16% of rheumatic disease patients without ILD [ 8 ]. With the high mortality rate in this patient population, any identifiable risk factors leading to respiratory failure and the need for intensive care unit-level care should be carefully addressed and managed in both inpatient and outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatic disease patients are usually considered immunosuppressed due to their underlying, malfunctioning immune system, which sometimes can be further exacerbated by the treatments they receive. A multicenter study in France found that the mortality rate of ILD patients with coexisting systemic rheumatic disease admitted to the intensive care unit was 40% compared to 16% of rheumatic disease patients without ILD [ 8 ]. With the high mortality rate in this patient population, any identifiable risk factors leading to respiratory failure and the need for intensive care unit-level care should be carefully addressed and managed in both inpatient and outpatient settings.…”
Section: Discussionmentioning
confidence: 99%